Dual Task Training Effects on Upper Extremity Functions and Performance of Daily Activities of Chronic Stroke Patients - JuHyung Park (Osong Public Health and Research Perspectives, 2019)
Objectives The purpose of this research was to study the influences of dual task training on upper extremity function and performance of daily activities of chronic stroke patients. Methods Dual task training was performed on 21 patients who had suffered a chronic stroke with hemiplegia. The dual task training was performed for 30 minutes per session, for 5 days a week, for 3 weeks. There were 5 evaluations carried out over 3 weeks before and after the intervention. Changes in upper extremity function were measured by using the Box and block test. Changes in the performance of daily activities were measured using the Korea-Modified Barthel Index. Results The mean upper limb function score of the chronic stroke patients increased significantly from 21.88 ± 19.99 before the intervention, to 26.22 ± 15.65 after the intervention (p < 0.05), and the mean daily activities score increased significantly from 65.82 ± 12.04, to 67.29 ± 12.90 (p < 0.05). Conclusion Dual task training effectively improved upper extremity function, and the performance of daily activities in chronic stroke patients.